2020
DOI: 10.1002/csr.2008
|View full text |Cite|
|
Sign up to set email alerts
|

How are service employees' perceptions of corporate social responsibility related to their performance? Prosocial motivation and emotional labor as underlying mechanisms

Abstract: Although interest in employees' perceptions of and their responses to corporate social responsibility (CSR) has grown up, it has been suggested that further research is necessary on how employees' perceptions of CSR are related to their performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 84 publications
1
14
0
1
Order By: Relevance
“…The present findings extend the micro‐CSR literature by underscoring the previously undiscovered relationship between frontline employee CSR perceptions and safety behaviors. Although a growing body of research has examined the role of frontline employee CSR perceptions in organizational and task behaviors, past studies have largely conceptualized positive task behaviors (e.g., creativity, job crafting, job performance, OCB, and service performance,) as outcomes of frontline employee CSR perceptions (e.g., Hur et al, 2018, 2019; Ko et al, 2018; Korschun et al, 2014; Shin & Hur, 2020). In this regard, this study is the first to have examined the positive effects of CSR perceptions on in‐role and extra‐role safety behaviors among frontline employees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present findings extend the micro‐CSR literature by underscoring the previously undiscovered relationship between frontline employee CSR perceptions and safety behaviors. Although a growing body of research has examined the role of frontline employee CSR perceptions in organizational and task behaviors, past studies have largely conceptualized positive task behaviors (e.g., creativity, job crafting, job performance, OCB, and service performance,) as outcomes of frontline employee CSR perceptions (e.g., Hur et al, 2018, 2019; Ko et al, 2018; Korschun et al, 2014; Shin & Hur, 2020). In this regard, this study is the first to have examined the positive effects of CSR perceptions on in‐role and extra‐role safety behaviors among frontline employees.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, managers should devise strategies to promote the CSR activities of their firms. Frontline employee CSR perceptions are related to not only in‐role and extra‐role safety behaviors but also a wide range of positive outcomes, including in‐role task behaviors and performance (e.g., Shin & Hur, 2020). Organizational CSR activities influence how external stakeholders perceive an organization as well as the self‐perceptions of internal audiences (i.e., employees) with respect to their organizational membership and attachment (Dutton et al, 2010; Ellemers et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with those from empirical research that perceived social capital positively correlated with subjective well-being, 72 , 73 specifically in the contexts of family and social media (Hwang et al, 2019). 63 , 74 Wise utilization of social media by professional sports franchises on building up perceived social capital among spectators is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies have indicated that the perception of CRS has an effect on a group’s prosocial behavior 61 and encourages employees in the service industry to be prosocially motivated. 62 , 63 Therefore, a person’s persistent prosocial behavior can be improved through CSR involvement. 64 Hypothesis 6 (H6) suggested that spectators’ perceived CSR during the sporting event would positively relate to their prosocial behavior.…”
Section: Introductionmentioning
confidence: 99%